Hi, umm pls help1/6(x-5)=1/2(x+6), solve for x And can you please explain

Accepted Solution

Answer: By solving the equation [tex]\frac{1}{6}(x-5)=\frac{1}{2}(x+6)[/tex] we found that   [tex]x=\frac{23}{2} \text { or }=11 \frac{1}{2}[/tex]Explanation:  Given equation, [tex]\frac{1}{6}(x-5)=\frac{1}{2}(x+6)[/tex] to find x  Step: 1 Cross multiply the denominators 2(x-5)=6(x+6)  Step: 2 Open brackets and simplify the term 2x-10=6x+36  Step: 3 Bring x terms on one side and simplify the equation the equation obtained is following,  2x-6x=36+10  -4x=46  [tex]-x=\frac{46}{4}=\frac{23}{2}=11 \frac{1}{2}[/tex]Therefore, we solved x value from the given equation [tex]\frac{1}{6}(x-5)=\frac{1}{2}(x+6)[/tex] as [tex]x=\frac{23}{2} \text { or }=11 \frac{1}{2}[/tex].